Establishment of Airhogem's Buko Nation in Montalban, Rizal - Maria Gemma C. Mendoza; Rhogelyn G. Tulang; Michael L. Protacio, Dem Cand (2019)
The proposed project will be known as AIRHOGEM's Buko Nation. This name AIRHOGEM is derived from the first syllable of proponents name, Al which stands for Alla, RHO which stands for Rhogelyn and GEM which stands for Gemma and the "Buko Nation' because AIRHOGEM's will offer different meals that made in buko or coconut The said business will offer different native dishes and desserts made from buko or coconut Buko is a tree of life and it is very popular fruit in some countries, most especially in the Philippines. It is a large fruit that has a thick shell with white flesh and liquid inside it and that grows on a palm tree. Buko is a fruit that is rich in Vitamin C. used in the prevention and treatment of scurvy and as an antioxidant for foods also called ascorbic acid. Some of the people thinks that Buko is just a simple fruit that can we just eat and drink, but they didn't know that we can make different meals in this. Some of the dishes that we offer is "Buko Pansit", "Buko Palabok", and "Buko Spaghetti" instead of using the regular noodles we replace it by the white flesh of the Buko to make it more nutritious and flavorful.
Undergraduate Thesis